Care coordination for older people in England: Does context shape approach?. (July 2019) - Abendstern, Michele; Jasper, Rowan; Hughes, Jane; Loynes, Nik; Sutcliffe, Caroline; Challis, David
Summary: Policy and practice developments in adult social care in England and elsewhere recognise the increasing role of the non-statutory sector. Care coordination services are central to the delivery of tailored support. This qualitative study focuses on support for older people and reports an analysis of 13 non-statutory sector services providing care coordination, grouped into four service types. Semi-structured interviews explored the influence of service context on the nature of practice. Findings: Particular elements of care coordination (e.g. assessment) were found to be shaped by the specific aims and purpose of each service type, such as extent to which they had a commissioning or provider role and the nature of their target group. Aspects of a range of case and care management approaches were in use throughout the sample, varying in relation to the distinct features of the service type. A set of overarching standards was found to be relevant to all services considered. Non-statutory sector services were found to provide innovative support which both complemented and sometimes substituted for the statutory sector. Applications: Findings point to the continued importance of social work values and methods to the work of non-statutory sector services providing care coordination and to current limitations in relation to what the sector can provide. These are issues which employers and service commissioners need to address to ensure that non-statutory sector services have the capacity and standards of practice to meet the demands made of them. Further areas of research are identified.